2010
DOI: 10.1111/j.1365-3083.2010.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ro/SSA Antibodies and Cardiac Arrhythmias in the Adult: Facts and Hypotheses

Abstract: It is well established that the passive trans‐placental passage of anti‐Ro/SSA antibodies from mother to foetus is associated with the risk to develop an uncommon syndrome named neonatal lupus (NLE), where the congenital heart block represents the most severe clinical feature. Recent evidence demonstrated that also adult heart, classically considered invulnerable to the anti‐Ro/SSA antibodies, may represent a target of the arrhythmogenicity of these autoantibodies. In particular, the prolongation of the QTc in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 68 publications
2
44
2
Order By: Relevance
“…The second theory involves electrophysiologic interference of antiRo/SSA antibodies with heart conduction (electrophysiological theory). 20 Consistent with these respective theories, steroids and i.v. immunoglobulins are used for anti-inflammatory treatment, while β-sympathomimetics are given for fetal pacing.…”
Section: Benefits and Risks Of Transplacental Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…The second theory involves electrophysiologic interference of antiRo/SSA antibodies with heart conduction (electrophysiological theory). 20 Consistent with these respective theories, steroids and i.v. immunoglobulins are used for anti-inflammatory treatment, while β-sympathomimetics are given for fetal pacing.…”
Section: Benefits and Risks Of Transplacental Treatmentsupporting
confidence: 62%
“…immunoglobulins are given as anti-inflammatory treatment, while β-sympathomimetics are used for fetal pacing. 20 A recent…”
mentioning
confidence: 99%
“…11,12 Interestingly, in the adult patients, anti-Ro Ab positivity is associated with repolarization abnormalities (QTc prolongation) [7][8][9][10] but not with conduction abnormalities (complete atrioventricular block), which is well described in children born to mothers with anti-Ro Abs. 13,14 Accordingly, it is assumed that the adult heart does not represent an immunological target for anti-Ro Abs.…”
mentioning
confidence: 99%
“…LVPs were recorded in patients with systemic lupus (Paradiso et al, 2001;Wranicz et al, 2001), and the depolarization abnormalities revealed by SAECG reflect a longer extent of myocardial fibrosis and echocardiography and SAECG alterations are markers of subclinical myocardial involvement. Increasing evidence suggest that anti-Ro/SSA antibodies may trigger rhythm disturbances due to an inhibiting cross-reaction with several cardiac calcium and potassium ionic channels (Lazzerini et al, 2010). So far, the evidence related to electrocardiographic disturbances in this setting is restricted to studies with small number of patients (Teixeira, et al, 2010).…”
Section: Connective Tissue and Systemic Diseasesmentioning
confidence: 99%
“…So far, the evidence related to electrocardiographic disturbances in this setting is restricted to studies with small number of patients (Teixeira, et al, 2010). The mechanisms of arrhythmias are related to the inflammatory process of pericarditis and myocarditis, atherosclerotic myocardial ischemia, increased sympathetic activity, vasculitis of small vessels with collagen deposits and anti-Ro/SSA antibodies (Lazzerini et al, 2010;Teixeira, et al, 2010). Cardiac sarcoidosis affects the myocardium, pericardium and endocardium, and the disease may present with: atrioventricular and intraventricular conduction disturbances, ventricular arrhythmias and HF.…”
Section: Connective Tissue and Systemic Diseasesmentioning
confidence: 99%